BISNIS PENGEMIS DALAM PERSPEKTIF PERATURAN DAERAH KALIMANTAN BARAT NO.11 TAHUN 2019 PASAL 37 DAN HUKUM ISLAM DI KOTA PONTIANAK - Agustini Agustini; Sukardi Sukardi; Suhardiman Suhardiman (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2021)
This research started from the phenomenon of beggars who became a social disease in Pontianak City. This work is not justified because it dramatically disturbs public order; a supporting factor that plays a role in handling beggars is Regional Regulation Number 11 of 2019 article 37 of the Pontianak City. The business of managing beggars is of particular interest to road users who pass at the redlight crossroad of the Kapuas 1 Highway Pontianak. This research is qualitative research with a qualitative approach to socio-legal research that uses descriptive methods. Data collection techniques used primary data consisting of observations, interviews, documentation, and secondary data obtained through literature, articles, journals, and the internet. The data analysis technique uses data collection, data reduction, data presentation, and conclusions, meanwhile, in testing the validity of the data using triangulation and member check. The results of the study show three findings: 1) The business of managing beggars is not appropriate based on positive law and Islamic law. 2) The implementation of Regional Regulation Number 11 of 2019 article 37 has not run optimally, the quality of service is still not well, and the sanctions given are not firm. 3) The view of Islamic law on the prohibition of giving beggars, there are three kinds of people who are permitted to beg, namely, people who bear a dependent, people who are afflicted by a disaster, and people who are stricken with disaster. Keyword: Beggars, Regional Regulations, Islamic Law, Pontianak City